2017
DOI: 10.1177/1087054717690810
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patterns, and Predictors of Sleep Problems and Daytime Sleepiness in Young Adolescents With ADHD

Abstract: Adolescents with ADHD commonly experience problems with daytime sleepiness that may significantly affect their functioning, but this may not be directly attributable to specific sleep problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 81 publications
(122 reference statements)
4
26
0
Order By: Relevance
“…Adolescents with ADHD were also more likely than adolescents without ADHD to report falling asleep in class. These findings are clinically meaningful since daytime sleepiness is common in adolescents with ADHD (Langberg et al., ) and associated with poorer academic performance in adolescents with ADHD (Langberg, Dvorsky, Marshall, & Evans, ). We also found that adolescents with ADHD were more likely than their peers to report having stayed up all night at least twice in the previous two weeks (15% and 5%, respectively).…”
Section: Discussionmentioning
confidence: 86%
“…Adolescents with ADHD were also more likely than adolescents without ADHD to report falling asleep in class. These findings are clinically meaningful since daytime sleepiness is common in adolescents with ADHD (Langberg et al., ) and associated with poorer academic performance in adolescents with ADHD (Langberg, Dvorsky, Marshall, & Evans, ). We also found that adolescents with ADHD were more likely than their peers to report having stayed up all night at least twice in the previous two weeks (15% and 5%, respectively).…”
Section: Discussionmentioning
confidence: 86%
“…This could be an extra source of distraction among pedestrians with ADHD. Moreover, other outcomes of ADHD, such as sleep disorders, substance misuse, and problems at workplace that may affect pedestrians awareness while crossing a road or walking in traffic environment [8,58,59]. An interesting study on risk factors for adverse driving outcomes in Dutch adults with ADHD demonstrated that alcohol use, and high levels of anxiety and hostility are highly prevalent among adults with ADHD interestingly discussing the mediating role of them on the risk for negative driving outcomes in drivers with ADHD [17].…”
Section: Adhd Comorbidities and Pedestrian Crash Injurymentioning
confidence: 99%
“…Recent estimates suggest that one in five children and young adults have difficulties sleeping (Calhoun et al, 2014). There is a rapidly rising prevalence of sleep problems among adolescents, which is associated with poor functioning (Langberg et al, 2017). Therefore, the increasing prevalence of sleep problems has become a recognized international public health problem (Gradisar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%